Delayed-onset akathisia due to amisulpride - Atmaca, Murad; Korkmaz, Sevda (Medknow Publications, 2011)
Despite the fact that second-generation antipsychotics have a lower potential to cause extrapyramidal side-effects, including akathisia, their incidence is not negligible. Recent work suggests that tardive akathisia may have pharmacological differences from acute akathisia. In the present study, we have evaluated the nature of delayed-onset akathisia in patients on amisulpride monotherapy. Overall, we screened 56 patients on amisulpride treatment for 2 months at a stabilized amisulpride dose. However, 18 patients with diagnostic and statistical manual of mental disorders-IV (DSM-IV) presented with acute or delayed-onset akathisia, and all of them also met the entry criteria. The patients were evaluated at baseline and at the time when akathisia presented clinically, with respect to the Positive and Negative Syndrome Scale and Barnes Akathisia Scale (BAS). Using the primary categorical criterion of akathisia (>= 2 points of the BAS global scale), 12 (21.4%) of the 56 patients experienced delayed-onset akathisia, and six (10.7%) showed acute akathisia. The mean time for onset of acute or delayed-onset akathisia was 5.8 +/- 2.1 and 39.4 +/- 11.3 days, respectively. The mean BAS scores at baseline and after the period of 2 months were 1.3 +/- 0.6 and 3.9 +/- 2.4, respectively (P < 0.001). Our results revealed that amisulpride could considerably lead to delayed-onset akathisia. However, studies comprising larger samples receiving different antipsychotics, and more comprehensive assessment, will help to ascertain the role of amisulpride in delayed-onset akathisia.
Keywords: Akathisia; amisulpride; delayed